2019
DOI: 10.1038/s41598-019-42245-3
|View full text |Cite
|
Sign up to set email alerts
|

PCC0208027, a novel tyrosine kinase inhibitor, inhibits tumor growth of NSCLC by targeting EGFR and HER2 aberrations

Abstract: PCC-0208027 is a novel tyrosine kinase inhibitor that has a strong inhibitory effect on epidermal growth factor receptor (EGFR)- or HER2-driven cancers. The aim is to assess the anti-tumor activity of PCC0208027 and related mechanisms in non-small cell lung cancer (NSCLC). We examined the activity of PCC0208027 on various mutated EGFRs, HER2, and HER4. MTT assays, flow cytometry, and Western blotting were used to examine the effects of PCC0208027 on NSCLC cells with different genetic characteristics and releva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…A higher hydrophobic contribution was found, due to a more deeply located binding pose inside the ATP binding site with respect to that observed in the wild type Erlotinib-EGFR complex. This contribution determined an increase of binding affinity and suggested an increasing Erlotinib inhibitory activity in presence of ELREA EGFR receptor, in agreement with experiment observations [33][34][35][36][37][38]. MD simulation trajectories revealed that this complex is very stable ( Figure S5) as confirmed by MM/PBSA binding energy values ( Figure 6).…”
Section: Erl and Egcg Binding With Egfr Elrea Deletionsupporting
confidence: 87%
See 1 more Smart Citation
“…A higher hydrophobic contribution was found, due to a more deeply located binding pose inside the ATP binding site with respect to that observed in the wild type Erlotinib-EGFR complex. This contribution determined an increase of binding affinity and suggested an increasing Erlotinib inhibitory activity in presence of ELREA EGFR receptor, in agreement with experiment observations [33][34][35][36][37][38]. MD simulation trajectories revealed that this complex is very stable ( Figure S5) as confirmed by MM/PBSA binding energy values ( Figure 6).…”
Section: Erl and Egcg Binding With Egfr Elrea Deletionsupporting
confidence: 87%
“…The results showed very good stability for the complexes of Erl and EGCG with wild type and ELREA deletion EGFR forms. In line with experimental data, it is well established the ability of Erlotinib to target TK of EGFR-ELREA [32], yet a significant benefit of Erl treatments was found also in patients with EGFR-wild type [33,34]. In addition, EGCG shows high growth inhibition activity towards EGFR-wt and ELREA harboring NLSC cell lines [35].…”
Section: Known Inhibitors Of Egfr-tk Domains Bind Differently With Thmentioning
confidence: 56%
“…Constitutive signaling from the EGFR promotes cell survival, proliferation [1], and invasiveness [2]. Aberrant EGFR signaling has been found in many human malignancies, including colorectal, lung, breast, and head and neck cancer [3,4]. Overexpression and activating mutations of EGFRs reported in up to 30% of solid tumors (including breast, colorectal, lung, pancreatic, gastric, head and neck cancer, and glioblastomas) generally correlate with a poor prognosis [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…This represents a new molecular targeted combination therapy for NSCLC patients with HER2 aberrations. Other HER target inhibitors, such as neratinib and PCC0208027, are also under-investigated, and further studies may provide more opportunities for treatment [ 52 , 53 ].…”
Section: Acquired Resistance and Corresponding Strategiesmentioning
confidence: 99%